2020
DOI: 10.3389/fendo.2020.610337
|View full text |Cite
|
Sign up to set email alerts
|

Teprotumumab as a Novel Therapy for Thyroid-Associated Ophthalmopathy

Abstract: Thyroid-associated ophthalmopathy (TAO) has remained a vexing and poorly managed autoimmune component of Graves’ disease where the tissues surrounding the eye and in the upper face become inflamed and undergo remodeling. This leads to substantial facial disfigurement while in its most severe forms, TAO can threaten eye sight. In this brief paper, I review some of the background investigation that has led to development of teprotumumab as the first and only US FDA approved medical therapy for TAO. This novel tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(95 reference statements)
1
3
0
Order By: Relevance
“… 9 , 39 This has led to the development of teprotumumab, a human IGF-1R inhibiting antibody, which is the only medication currently approved by the US FDA for the treatment of TAO. 14 , 40 , 41 We obtained similar results to those obtained by teprotumumab in a mouse model of TAO treated with miR-143. HE staining indicated a reduction in the volume of adipose tissue and reduced levels of inflammation in response to the overexpression of miR-143.…”
Section: Discussionsupporting
confidence: 80%
“… 9 , 39 This has led to the development of teprotumumab, a human IGF-1R inhibiting antibody, which is the only medication currently approved by the US FDA for the treatment of TAO. 14 , 40 , 41 We obtained similar results to those obtained by teprotumumab in a mouse model of TAO treated with miR-143. HE staining indicated a reduction in the volume of adipose tissue and reduced levels of inflammation in response to the overexpression of miR-143.…”
Section: Discussionsupporting
confidence: 80%
“…3 Teprotumumab, one type of anti-IGF-1R, was FDA approved in 2020 for the treatment of adults with active TED. 16 It demonstrates efficacy for proptosis reduction in cases of active and chronic TED 15,16,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] ; however, the potential therapeutic and side effect profile of this class of medication, especially as it relates to the eye has not been fully elucidated. The FDA lists the following common systemic adverse reactions for teprotumumab: muscle spasm, hearing loss, hyperglycemia, nausea, alopecia, diarrhea, dry skin, dysgeusia, headache, and fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The Horizon Therapeutics Phase 3 clinical trial reported that teprotumumab, an IGF-1R antibody, demonstrated improvement in proptosis, clinical activity score (CAS), diplopia response, and Graves' ophthalmopathy-specific quality of life (GO-QOL) scores in patients with active TAO when compared with placebo. 15,16,[19][20][21][22][23][24][25][26][27][28][29][30][31] Several case reports and 1 case series describe teprotumumab induced improvement in TAO-associated optic neuropathy, with some patients demonstrating improved visual acuity, visual fields, CAS, proptosis, and extraocular size with just 1 or 2 infusions. [32][33][34][35][36] Teprotumumab has also been demonstrated to improve proptosis, CAS, and diplopia in patients with stable, chronic TED.…”
Section: Figmentioning
confidence: 99%
“…Now with real world experience, numerous publications have documented that teprotumumab works in a wide variety of patients not included in the original clinical trials, including those with inactive or noninflammatory disease, TED-related optic neuropathy, previous surgery, and longer duration of disease (chronic). This suggests that the relationship between the thyroid-stimulating hormone receptor (TSH-R) and the insulin-like growth factor-1 receptor (IGF-1R) is unaltered by the duration of disease, current disease activity, previous surgery, or the specific manifestations of the patient's TED 1,10–33…”
Section: Indications For Usementioning
confidence: 99%